CD177 modulates the function and homeostasis of tumor-infiltrating regulatory T cells - Myung-Chul Kim (Nature Portfolio, 2021)
Regulatory T (Treg) cells are important modulators of the tumor microenvironment. Here the authors perform transcriptome profiling of immune cells from patients with renal clear cell carcinoma to find a Treg signature that correlates with poorer prognosis, with CD177 being implicated as the main mediator for related alterations in Treg activity and tumor outcome.